ANALISIS RASCH MODEL DESAIN DIDAKTIS PEMBELAJARAN ETNOMATEMATIKA SUNDA MELALUI PERMAINAN ENGKLEK DALAM MENGEMBANGKAN KEMAMPUAN PEMODELAN MATEMATIK DI KELAS 5 SEKOLAH DASAR - Mutiara Adha, - (2020)
Learning mathematics in schools to prepare students with various types of abilities and one of the abilities of mathematical modeling, which is to connect between students with everyday life with a mathematical concept generated from the modeling, so that it can provide assistance and support students for learning mathematics. However, when studying in the field, researchers still find teaching materials that only use the ability to memorize formulas or how to calculate and concept only. While other types of abilities such as those stated by Sumarmo and Hendriana (2014) must be possessed by students, which are very important, especially in learning mathematics. This research is a quantitative descriptive study that aims to describe the results of the Rasch Model analysis of the didactic design of Sundanese ethnomatematics learning through engklek games in developing mathematical modeling abilities in grade 5 elementary schools. The secondary data research instrument used was the learning barrier test instrument, the initial design didactic student worksheet, and revision didactic design student worksheet the Sundanese ethnomatematics through engklek games on grade 5 school students, and supporting data used were teacher questionnaire. Data analysis used in this research is the Rasch Model analysis with the help of Winstep software version 4.5.2, which interprets the data from the calculation results of the statistical summary table, person fit order, person measure, and person-item map. The results showed the analysis using the Rasch Model analysis for the student learning constraint test was smaller than the difficulty level of the questions and students' abilities were higher than the difficulty level of the questions needed in the initial didactic design and revision didactic design. Keywords: Rasch Model Analysis of the Didactic Design